Solid-phase synthesis of JBIR-126 (Tambromycin), JBIR-35 and their analogs. (13th April 2021) - Midde, Sreekanth; Vytla, Devaiah; Velayuthaperumal, Rajeswari; Kaliyaperumal, Kumaragurubaran; Reddy, China Anki; Jarugu, Lokesh Babu; Gupta, Anuradha; Roy, Amrita; Mathur, Arvind
Graphical abstract: Highlights: Solid-phase synthesis of JBIR-126 (Tambromycin) and JBIR-35. Rapid assembly of several analogs on solid phase for SAR. Oxazoline ring tolerated on the solid support, CTC-resin. Acid mediated global deprotection. Abstract: The convenience of solid-phase synthesis over solution phase synthesis is well known for peptides for the ease of performing reactions as well as isolation of products. Herein we describe the Fmoc-solid-phase synthesis of natural products JBIR-126 (Tambromycin), JBIR-35 and their analogs. These compounds were prepared by the incorporation of several amino acids at the two possible amidation sites. For the serine terminal region both serine and methyl serine were employed and for the middle segment, flanked by serine region and dihydroisoxazole, different commercially available Fmoc-amino acids and synthesized Fmoc-tambroline were utilized.